PENGARUH MEDIA PEMBELAJARAN KARTU SUKU KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS 1 SD INPRES 16 KABUPATEN SORONG - Suci Ramadayanti T. Pakaya; Desti Rahayu; Anis Alfian Fitriani (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aimas to find out how the results of syllable and learning media affect the intial reading ability og grade I studentes of SD Inpres 16 sorong regerency. This type of research is quantitative research and uses the one group Pre-test Post-test design. The population of this study is all student in grade I of SD Inpres 16 Sorong Regerency for the 2024 academic year. The sampel used was 38 students. The sampling technique is a saturated sampling technique. The data collection technique uses observation sheets and performance tests (pretest and posttest). The resulst of the study showed that the value of the intial reading ability of pretest students before using syllable car media was 0.856 and after the treatment of intial reading ability of the posttest was 0,882 and was in the very good category. From these results, there awas a significant difference in the ability to read beginning before and after using the syllable card media.